Combined In Silico and In Vitro Approach Predicts Low Wall Shear Stress Regions in a Hemofilter that Correlate with Thrombus Formation In Vivo. Issue 2 (March 2018) - Buck, Amanda K. W.; Groszek, Joseph J.; Colvin, Daniel C.; Keller, Sara B.; Kensinger, Clark; Forbes, Rachel; Karp, Seth; Williams, Phillip; Roy, Shuvo; Fissell, William H.
Abstract : A major challenge in developing blood-contacting medical devices is mitigating thrombogenicity of an intravascular device. Thrombi may interfere with device function or embolize from the device to occlude distant vascular beds with catastrophic consequences. Chemical interactions between plasma proteins and bioengineered surface occur at the nanometer scale; however, continuum models of blood predict local shear stresses that lead to platelet activation or aggregation and thrombosis. Here, an iterative approach to blood flow path design incorporating in silico, in vitro, and in vivo experiments predicted the occurrence and location of thrombi in an implantable hemofilter. Low wall shear stress (WSS) regions identified by computational fluid dynamics (CFD) predicted clot formation in vivo . Revised designs based on CFD demonstrated superior performance, illustrating the importance of a multipronged approach for a successful design process.